73.7k views
4 votes
Which equation has a graph that is perpendicular to the graph of -x + 6y = -12?

a. x + 6y = -67
b. x - 6y = -52
c. 6x + y = -52
d. 6x - y = 52

User Jmathewt
by
5.8k points

2 Answers

6 votes

C

Explanation:

Let
l_(1) be the equation of the line with slope
m_(1) and let
l_(2) be the equation of the line with slope
m_(2).

As we know,for two lines
l_(1) and
l_(2) to be perpendicular,


m_(1)* m_(2) =-1

In the given problem,slope of given line=
m_(1)=
(-6)/(-1)=6

For option a,slope =
m_(2)
=(-6)/(1) =-6

In this case,
m_(1)* m_(2)=6* -6=-36

So,option a is incorrect.

For option b,slope =
m_(2)
=(6)/(1) =6

In this case,
m_(1)* m_(2)=6* 6=36

So,option b is incorrect.

For option c,slope =
m_(2)
=(-1)/(6) =(-1)/(6)

In this case,
m_(1)* m_(2)=6* (-1)/(6)=-1

So,option c is correct.

For option d,slope =
m_(2)
=(1)/(6) =(1)/(6)

In this case,
m_(1)* m_(2)=6* (1)/(6)=1

So,option d is incorrect.

User Costi Muraru
by
6.0k points
6 votes

Answer:

c) 6x + y = -52 is required equation perpendicular to the given equation.

Explanation:

If the equation is of the form : y = mx + C.

Here m = slope of the equation.

Two equations are said to be perpendicular if the product of their respective slopes is -1.

Here, equation 1 : -x + 6y = -12

or, 6y = -12 + x

or, y = (x/6) - 2

Slope of line 1 = (1/6)

Now, for equation 2 to be perpendicular:

Check for each equation:

a. x + 6y = -67 ⇒ 6y = -67 - x

or, y = (-x/6) - (67/6) ⇒Slope of line 2 = (-1/6)

but
(1)/(6) * (-1)/(6)  \\eq -1

b. x - 6y = -52 ⇒ -6y = -52 - x

or, y = (x/6) + (52/6) ⇒Slope of line 2 = (1/6)

but
(1)/(6) * (1)/(6)  \\eq -1

c. 6x + y = -52

or, y =y = -52 - 6x ⇒Slope of line 2 = (-6)


(1)/(6) * (-6)  =  -1

Hence, 6x + y = -52 is required equation 2.

d. 6x - y = 52 ⇒ -y = 52 - 6x

or, y = 6x - 52 ⇒Slope of line 2 = (6)

but
(1)/(6) * 6  \\eq -1

Hence, 6x + y = -52 is the only required equation .

User James Carter
by
5.3k points